2014
DOI: 10.1016/j.ypmed.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative effectiveness study of Healthy Directions 2—A multiple risk behavior intervention for primary care

Abstract: Objective To evaluate the effectiveness of the Healthy Directions 2 (HD2) intervention in the primary care setting. Methods HD2 was a cluster randomized trial (conducted 3/09 – 11/11). Primary sampling unit was provider (n=33), with secondary sampling of patients within provider (n=2,440). Study arms included: 1) usual care (UC); 2) HD2-- a patient self-guided intervention targeting 5 risk behaviors; or 3) HD2 plus 2 brief telephone coaching calls (HD2+CC). The outcome measure was proportion of participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…MHBC focuses on promoting multiple health behaviors either simultaneously or sequentially within a limited time period to improve efficiency because health risk behaviors often cluster (Prochaska, Spring, & Nigg, 2008). Although many MHBC intervention studies conducted in the past met with limited success (Prochaska et al, 2008), more positive results have been reported in recent literature (Emmons et al, 2014; Green, Hayman, & Cooley, 2015). In a recent systematic review of MHBC interventions for cancer survivors, Green et al (2015) found that in-person interventions consistently produced changes in diet, exercise, and smoking, and interventions using phone or mail contact with longer durations also showed promising results.…”
Section: Discussionmentioning
confidence: 99%
“…MHBC focuses on promoting multiple health behaviors either simultaneously or sequentially within a limited time period to improve efficiency because health risk behaviors often cluster (Prochaska, Spring, & Nigg, 2008). Although many MHBC intervention studies conducted in the past met with limited success (Prochaska et al, 2008), more positive results have been reported in recent literature (Emmons et al, 2014; Green, Hayman, & Cooley, 2015). In a recent systematic review of MHBC interventions for cancer survivors, Green et al (2015) found that in-person interventions consistently produced changes in diet, exercise, and smoking, and interventions using phone or mail contact with longer durations also showed promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy Directions 2 (HD2) study was a cluster-randomized controlled trial of a self-guided, multiple risk behavior (MRB) intervention conducted in two urban health centers (conducted from 3/2009–11/2011) in the Boston, Massachusetts, area that has been described elsewhere (Emmons et al, 2014; Greaney et al, 2014). Briefly, English-speaking patients 18+ years of age with scheduled well visits or chronic disease management appointments at the participating health centers were sent a study introduction letter prior to their scheduled appointments.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the two intervention conditions led to greater improvements in MRB score than usual care, although there was no significant difference between the two intervention conditions. At 6 months, 28% of participants randomized to usual care had improvements in their MRB scores versus 39% of those randomized to the HD2 intervention materials and 43% of those randomized in the HD2 intervention materials plus coaching calls (Emmons et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Algorithms developed by Emmons and colleagues from the previous Healthy Directions intervention were used to guide increases in physical activity over time. 16,31…”
Section: Methodsmentioning
confidence: 99%